Comparison between the use of Titanium Clips and Monopolar Diathermy for Closure of the Mesoappendix in Laproscopic Appendectomy in terms of Operative Time and Cost - Akhtar, Shahzad; Farrani, Tariq Mukhtar; Hussain, Mukarram; Yousaf, Muhammad; Jabbar, Ghazanfar; Makshoof, Talha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the use of Titanium clips and Monopolar diathermy for laparoscopic appendectomy mesoappendix closure in terms of operative time and cost.Study Design: Quasi-experiment study.Place and Duration of Study: Department of Surgery, Combined Military Hospital, Nowshera Pakistan, from Jul 2021 to Jun 2022.Methodology: A total of 70 patients who were diagnosed with acute appendicitis and were admitted for laparoscopic appendectomy were randomly divided into two groups via the lottery method. In Group-A, the closure of the mesoappendix was done using Titanium clips, and in Group-B, the ligation of the mesoappendix was done using Monopolar diathermy. Patient outcomes in terms of operative time and procedure cost were assessed.Results: Out of 70 patients, 49(70.0%) were males and 21(30.0%) were females, aged 18 to 60 years, with a mean age of 37.57±7.71 years. The overall mean weight of the patients was 65.29±12.14 kg; height was 1.71±0.12 metres; and BMI was 24.96±5.23 kg/m2, respectively. Prolonged operative time was observed in 16(45.71%) patients in Group-A, compared to 7(20.0%) in Group-B (p-value 0.022). In Group-A, the total cost of the operation was Rs. 32,000, whereas in Group-B, it was Rs. 30,000 (p-value=0.001).Conclusion: This study concluded that Monopolar diathermy for the closure of the mesoappendix is better in terms of operating time and cost as compared to the use of Titanium clips.